2022
DOI: 10.3389/fmed.2022.840024
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Verification of Prognostic Nomograms for Young Women With Breast Cancer Bone Metastasis

Abstract: PurposeThe prognosis of patients with metastatic breast cancer usually varies greatly among individuals. At present, the application of nomogram is very popular in metastatic tumors. The present study was conducted to identify independent survival predictors and construct nomograms among young women with breast cancer bone metastasis (BCBM).Patients and MethodsWe searched the Surveillance, Epidemiology, and End Results (SEER) database to identify young women diagnosed with BCBM between 2010 and 2016. We first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
4
3
Order By: Relevance
“…Many studies have suggested that histological subtype, primary site, and BC subtype are independent predictors of BC patient diagnosis or prognosis (11)(12)(13). In this study, although simple analysis indicated that these variables might affect the diagnosis and prognosis of MBCBM patients, multivariate analysis revealed no significance (P>0.05).…”
Section: Malignant Tumor Cells Interfere With Bone Microenvironment H...contrasting
confidence: 64%
See 2 more Smart Citations
“…Many studies have suggested that histological subtype, primary site, and BC subtype are independent predictors of BC patient diagnosis or prognosis (11)(12)(13). In this study, although simple analysis indicated that these variables might affect the diagnosis and prognosis of MBCBM patients, multivariate analysis revealed no significance (P>0.05).…”
Section: Malignant Tumor Cells Interfere With Bone Microenvironment H...contrasting
confidence: 64%
“…However, many studies in recent years have shown that primary tumor surgery can also be used as palliative care to control tumor burden and provide survival benefits for patients with metastatic BC (31). Studies have shown that chemotherapy or radiotherapy in FBC patients with BM could alleviate cancer-related symptoms and improve survival benefits (11,12). However, in our multivariate analysis, chemotherapy and radiotherapy did not significantly enhance the prognosis in MBCBM patients (P>0.05).…”
Section: Malignant Tumor Cells Interfere With Bone Microenvironment H...contrasting
confidence: 62%
See 1 more Smart Citation
“…However, there is a lack of accurate prediction models in the clinic. Recently, some studies used nomograms to make several survival prediction models for patients with BMBC ( 7 – 12 ), but their accuracy rate is only about 70%. As a result, a more accurate and powerful model is needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no accurate prediction model for them. The most used model for predicting the survival rate is nomogram, but its accuracy rate is only about 70% (7)(8)(9)(10)(11)(12). As a result, a more accurate and powerful model is needed.…”
Section: Introductionmentioning
confidence: 99%